Effectiveness of Ipragliflozin for Reducing Hemoglobin A1c in Patients With a Shorter Type 2 Diabetes Duration: Interim Report of the ASSIGN-K Study - Iemitsu, Kotaro (J Clin Med Res, 2017)
BACKGROUND: Ipragliflozin is a selective sodium glucose co-transporter 2 inhibitor. The ASSIGN-K study is investigating the efficacy and safety of ipragliflozin for type 2 diabetes mellitus (T2DM) in the real-world clinical setting. METHODS: Japanese T2DM patients with inadequate glycemic control despite diet and exercise with/without pharmacotherapy were enrolled in an investigator-driven, multicenter, prospective, observational study examining the efficacy and safety of ipragliflozin treatment (50 mg/day for 52 weeks). We performed interim analysis after 24 weeks. RESULTS: In 367 patients completing 24-week ipragliflozin therapy, hemoglobin A1c (HbA1c) decreased significantly from 8.07% at baseline to 7.26% in week 24 (P < 0.001). The change in HbA1c from treatment initiation to week 24 was -0.88% in patients < 65 years old versus -0.55% in those ≥ 65 years and -0.92% in men versus -0.70% in women (all P < 0.001). When baseline HbA1c was < 7%, 7% to < 8%, and ≥ 8%, the change was -0.18%, -0.45%, and -1.48%, respectively (P = 0.5352, P < 0.001, and P < 0.001, respectively). When baseline body mass index (BMI) was < 25, 25 to < 30, and ≥ 30, the change was -1.05%, -0.65%, and -0.87%, respectively (all P < 0.001). Multiple regression analysis showed that HbA1c decreased more in patients with a higher baseline HbA1c or shorter duration of diabetes. An HbA1c < 7% was achieved in 33.3% of the patients, and their baseline HbA1c was significantly lower than that of patients failing to achieve it (P < 0.001). Adverse events (AEs) occurred in 106/451 patients (23.5%), including 29.1% of patients aged 65 or older. Common AEs were vulvovaginal candidiasis (3.1%) and genital pruritus (1.8%). Serious AEs included urinary tract infection, unstable angina, and ketosis, which occurred in patients who did not suspend medication during acute illness. CONCLUSIONS: Ipragliflozin significantly improved HbA1c in T2DM patients with inadequate glycemic control. Improvement in HbA1c was significant irrespective of age, sex, baseline HbA1c, or BMI, but efficacy was greater with a higher baseline HbA1c and shorter duration of diabetes. For safe continuation of treatment, patients should be advised to suspend medication during acute illness.